P05 Safety, tolerability, and immunogenicity of V114 compared with PCV13 in preterm infants: a pooled subgroup analysis of four Phase III studies. (19th January 2023) - Banniettis, Natalie; Chapman, Timothy J; Xu, Shengjie; Lupinacci, Robert; Shi, Yaru; Shekar, Tulin; Flores, Sheryl A; Feemster, Kristen; Yi, Jumi; McFetridge, Richard; Kaminski, Janusz; Bickham, Kara; et al.
Abstract: Background: Risk of invasive pneumococcal disease is 3-fold higher in preterm versus full-term infants, mainly due to underlying comorbidities and immunological immaturity. V114 is a 15-valent pneumococcal conjugate vaccine (PCV) containing the 13 serotypes in 13-valent PCV (PCV13) plus two additional serotypes, 22F and 33F. A pooled subgroup analysis was performed in preterm infants (<37 weeks gestational age) enrolled in 4 paediatric Phase III studies evaluating the safety and immunogenicity of different 4-dose regimens of V114 or PCV13. Methods: Safety was evaluated as the proportion of participants with AEs following each vaccination. Serotype-specific anti-pneumococcal IgG GMCs, IgG response rates, and OPA GMTs were measured at 30 days post-primary series (PPS; post-dose 3 [PD3]), pre-toddler dose, and 30 days post-toddler dose (PTD; post-dose 4 [PD4]). Results: 174 and 180 participants received V114 and PCV13, respectively. Mean gestational age was 35.4 weeks (range: 27–37 weeks). Proportions of participants with any AE were comparable between vaccination groups following each vaccination; most solicited AEs were transient (≤3 days) and of mild-to-moderate intensity. V114-elicited IgG GMCs (Figure 1), IgG response rates, and OPA GMTs were generally comparable to PCV13 for the 13 shared serotypes and higher for serotypes 22F and 33F at 30 days PPS (PD3) and PTD (PD4). Conclusions: In preterm infants, vaccination with V114 has an acceptable safety profile, is well tolerated, and induces comparable immune responses to PCV13 for the 13 shared serotypes and higher immune responses to V114 serotypes 22F and 33F. Study results support use of V114 in preterm infants. Figure 1. Summary of IgG GMCs from pooled analysis (per-protocol population).